Achieving Competitive Advantage through Knowledge Management Practices: Knowledge-Based View (KBV) Strategy on Indonesia Electricity Sector - Khusnul Rofida Novianti (APMBA (Asia Pacific Management and Business Application), 2019)
Knowledge being the most valuable intangible assets that became source of competitive advantage of the firm since the emergence of knowledge management replace assets management concepts. This makes the paradigm shift from resource-based competitiveness to knowledge-based competitiveness, from RBV to KBV. This  research aims to analyze knowledge management practices through Knowledge-Based View (KBV) to gain competitive advantage in Indonesia electricity sector, namely PT PLN (Persero),  one of State-Owned Enterprise with the biggest amount of assets in Indonesia energy sector .This study used a qualitative approach with post-positivism paradigm and research design using case study (single case study). Data obtained through interviews, direct observation, document, archive and website review.The results showed that the competitive advantage was achieved by knowledge sharing as the organizational culture of PT PLN (Persero), KM in an effort to improve individual and organizational performance and by maximizing the role of KM. The challenge of Knowledge Management comes from internal and external sources like gap generation differences, high rotation of employees without the support of adequate knowledge transfer, selection of suitable knowledge transfer methods, lack of documentation of knowledge transfer and data availability of energy resources.